Epithelial–Mesenchymal Transitioned Circulating Tumor Cells Capture for Detecting Tumor Progression - Satelli, Arun; Mitra, Abhisek; Brownlee, Zachary; Xia, Xueqing; Bellister, Seth; Overman, Michael J.; Kopetz, Scott; Ellis, Lee M.; Meng, Qing H.; Li, Shulin (Clinical cancer research, 2015)
Purpose: This study aimed to detect cell-surface vimentin (CSV) on the surface of epithelial–mesenchymal transitioned (EMT) circulating tumor cells (CTC) from blood of patients with epithelial cancers. Experimental Design: In this study, 101 patients undergoing postsurgery adjuvant chemotherapy for metastatic colon cancer were recruited. EMT CTCs were detected from blood of patients using the 84-1 monoclonal antibody against CSV as a marker. EMT CTCs isolated were characterized further using EMT-specific markers, fluorescent in situ hybridization, and single-cell mutation analysis. Results: Using the 84-1 antibody, we detected CSV exclusively on EMT CTCs from a variety of tumor types but not in the surrounding normal cells in the blood. The antibody exhibited very high specificity and sensitivity toward different epithelial cancer cells. With this antibody, we detected and enumerated EMT CTCs from patients. From our observations, we defined a cutoff of <5 or ≥5 EMT CTCs as the optimal threshold with respect to therapeutic response using ROC curves. Using this defined threshold, the presence of ≥5 EMT CTCs was associated with progressive disease, whereas patients with <5 EMT CTCs showed therapeutic response. Conclusion: Taken together, the number of EMT CTCs detected correlated with the therapeutic outcome of the disease. These results establish CSV as a universal marker for EMT CTCs from a wide variety of tumor types and thus provide the foundation for emerging CTC detection technologies and for studying the molecular regulation of these EMT CTCs. Clin Cancer Res; 21(4); 899–906. ©2014 AACR.